Ideas of quantum chemistry. - Piela, Lucjan, 1943- (Elsevier, 2020)
"Ideas of Quantum Chemistry, Volume One: From Quantum Physics to Chemistry shows how quantum mechanics is applied to molecular sciences to provide a theoretical foundation. Organized into digestible sections and written in an accessible style, it answers questions, highlighting the most important conclusions and essential mathematical formulae. Beginning with an introduction to the magic of quantum mechanics, the book goes on to review such key topics as the Schrodinger Equation, exact solutions, and fundamental approximate methods. The crucial concept of molecular shape is then discussed, followed by the motion of nuclei and the orbital model of electronic structure. This updated volume covers the latest developments in the field and can be used either on its own as a detailed introduction to quantum chemistry or in combination with Volume Two to give a complete overview of the field"--Publisher's description.